The Use Of Augmented Reality (AR) Media To Enhance Student Motivation Learning - Pranahadi, Tatag Yudha; Yani, Indri; Nefosano, Hedi (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2024)
This study aims to increase student learning motivation using Augmented Reality (AR) media in the context of science learning. The research method used was collaborative classroom action research with research subjects consisting of XI MIPA 1 students at SMA Negeri 9 Bogor City. This study used learning motivation questionnaires as a measuring tool, with indicators that included confidence in self-ability, learning strategies that activate students, the meaning of science learning, achievement, and learning environment stimuli. Augmented Reality media was developed using the Halo AR application and applied to learning plant tissue structure and function material (KD 3.3 and 4.3) and animal tissue structure and function (KD 3.4 and 4.4). The results showed that the application of AR media in learning has succeeded in increasing the average learning motivation of students by 0.6 points, which increased from 2.41 to 3.01 in the 2nd action cycle. Based on the results of this collaborative classroom action research, it can be concluded that the use of Augmented Reality media is effective in increasing the learning motivation of students in class XI MIPA 1 at SMA Negeri 9 Kota Bogor. These results make an important contribution to developing innovative and more engaging learning strategies and can lay the foundation for developing broader technology-based education in the future.